Low Maternal Capital Predicts Life History Trade-Offs in Daughters: Why Adverse Outcomes Cluster in Individuals - Wells, Jonathan C. K.; Cole, Tim J.; Cortina-Borja, Mario; Sear, Rebecca; Leon, David A.; Marphatia, Akanksha A.; Murray, Joseph; Wehrmeister, Fernando C.; Oliveira, Paula D.; Gonçalves, Helen; Oliveira, Isabel O.; Menezes, Ana Maria B. (Frontiers in Public Health, 2019)
Background: Some individuals appear prone to multiple adverse outcomes, including poor health, school dropout, risky behaviour and early reproduction. However, this clustering remains poorly understood. Drawing on evolutionary life history theory, we hypothesised that the magnitude of maternal investment in early life would predict the developmental trajectory and adult phenotype of female offspring. Specifically, we predicted that daughters receiving low investment would prioritise the life history functions of ‘reproduction’ and ‘defence’ over ‘growth’ and ‘maintenance’, increasing the risk of several adverse outcomes. Methods: We analysed data on mother-daughter dyads (n=2091) from a birth cohort in Pelotas, Brazil. We combined data on maternal height, body mass index, income and education into a composite index of ‘maternal capital’. Daughter outcomes included reproductive status at 18 years, growth, adult anthropometry and body composition, cardio-metabolic risk, educational attainment, work status and risky behaviour. We tested whether early reproduction by daughters (<18 years), and exposure to low maternal capital, were associated with adverse daughter outcomes. We then tested whether these associations accounted for the clustering of adverse outcomes among daughters. Results: Daughters reproducing early were shorter, more centrally adipose, had less education and demonstrated more risky behaviour compared to those not reproducing early. Low maternal capital was associated with an increased likelihood of the daughter reproducing early, smoking and having committed violent crime. High maternal capital was positively associated with the daughter’s birth weight and adult size, and the likelihood of being in school. Associations of maternal capital with cardio-metabolic risk were inconsistent. Daughters reproducing early comprised 14.8% of the population, but accounted for 18% of obesity; 20% of violent crime, low birth weight and short stature; 32% of current smoking; and 52% of school dropout. Exposure to low maternal capital contributed similarly to the clustering of adverse outcomes among daughters. Conclusion: Consistent with life history theory, daughters exposed to low maternal capital demonstrated ‘future discounting’ in both behaviour and physiology, prioritising early reproduction over growth, education and health. Trade-offs associated with low maternal capital and early reproduction contribute to the clustering of adverse outcomes. Our approach provides new insight into inter-generational cycles of disadvantage.